2018
DOI: 10.1063/1.5044659
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of parametric instabilities in nonlinear parabolic multimode fibers

Abstract: We provide a systematic analysis of geometric parametric instabilities in nonlinear graded-index multimode fibers. Our approach implicitly accounts for self-focusing effects and considers dispersion processes to all orders. It is shown that the resulting parametric problem takes the form of a Hill’s equation that can be systematically addressed using a Floquet approach. The theory developed indicates that the unstable spectral domains associated with such geometric parametric instabilities can be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In order to unravel the origin of this flat supercontinuum generation, it is imperative to first understand how FWM processes or geometric parametric instabilities 22,28,51 unfold in a uniform graded-index nonlinear MMF. This analysis is pertinent to CW (or in our case broad pulses) excitations in the normal dispersive region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to unravel the origin of this flat supercontinuum generation, it is imperative to first understand how FWM processes or geometric parametric instabilities 22,28,51 unfold in a uniform graded-index nonlinear MMF. This analysis is pertinent to CW (or in our case broad pulses) excitations in the normal dispersive region.…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, has a profound effect on the spectral perturbations A ( z ,Ω) located at the sidebands ω 0 ± Ω around the carrier frequency ω 0 . Under these conditions, these perturbations obey the following Hill’s equation 51 :where β e = [ β ( ω 0 + Ω)+ β ( ω 0 −Ω)]/2− β ( ω 0 ) involves all the even terms of the Taylor series expansion of the dispersion profile β ( ω ). In the above equation, represents a normalized propagation distance, n 2 accounts for the Kerr nonlinear index coefficient, and k 0 = 2π/ λ 0 , with λ 0 being the pump wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Notable predictions of the VA are that the SSI period z s is independent of power, whereas the amplitude of the beam intensity and width oscillations is power-dependent. An important consequence of the invariance of z s is that the position of GPI sidebands remains a constant, as the beam power is increased [8,26]. In this work, we advance the theory of SSI in GRIN MMFs, by deriving an exact solution for the nonlinear evolution of first and second order moments of a laser beam of arbitrary shape.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of this effort, a number of intriguing processes have been observed that have no counterpart whatsoever in single-mode settings. These include for example, geometric parametric instabilities [11][12][13][14] , spatiotemporal mode-locking 10 , efficient supercontinuum generation 12,15 , and the formation of multimode solitons along with a novel class of Cherenkov dispersive wave lines 16,17 , to mention a few. In the same vein, in three independent studies, a peculiar effect was found to take place in such nonlinear multimode environments whereby the optical power gradually flowed towards the lowest group of modes 12,18,19 .…”
mentioning
confidence: 99%